A Prospective Comparison of Serum and Transcutaneous Bilirubin in Indian Neonates - Kumar, Durgesh; Kumar, Dinesh (Journal of Pediatric Intensive Care, 2020)
The objective of this study was to compare the transcutaneous bilirubin (TcB) with total serum bilirubin (TSB) and to find out the effect of phototherapy on correlation of TcB and TSB during and after phototherapy in Indian neonates. Prospective observational study was performed at neonatal intensive care unit of Uttar Pradesh University of Medical Sciences, Saifai, Etawah, India. Blood samples for TSB estimation of 276 jaundiced neonates were sent, and simultaneously, TcB was measured at forehead and sternum on admission and 12 hourly till discontinuation of phototherapy as per the American Academy of Pediatrics nomogram chart and their correlation was assessed. The effect of phototherapy on correlation of TcB and TSB during and after phototherapy was also observed. The correlation between TSB and TcB was linear and significant for the entire study population over forehead (Pearson's r = 0.802, R2 = 0.644, p < 0.001) as well as over sternum (Pearson's r = 0.825, R2 = 0.681, p < 0.001) before starting the phototherapy. This correlation becomes slightly lower for TSB versus TcB forehead (Pearson's r = 0.753, R2 = 0.568, p < 0.001) and for TSB versus TcB sternum (Pearson's r = 0.754, R2 = 0.569, p < 0.001) after giving phototherapy for at least 24 hours. The correlation coefficients for TSB versus TcB measurements over forehead and sternum were 0.758 and 0.806, respectively, after 36 hours of phototherapy. TcB measurements using the transcutaneous bilirubinometer correlate closely with TSB levels, so it can be used as an easy and rapid noninvasive method of bilirubin measurement in jaundiced neonates.
Keywords: transcutaneous bilirubin; total serum bilirubin; neonates; phototherapy